Pergulatan Doktrin dan Realitas dalam Proses Teoretisasi Ekonomi Islam - Hafas Furqani (Islamica: Jurnal Studi Keislaman, 2016)
This article examines the struggle between the doctrine and reality in the process of theorizing Islamic economics that until now remains a challenge in building the science of Islamic economics. The process of theorizing is a problem of epistemology and methodology. As a discipline in the realm of social sciences, Islamic economics uses authoritative sources of Islam (al-Qur’ân and Hadîth), logic and empirical experience. Islamic economic theory is expected to grow from all three of these sources. In contrast to conventional economic theory, the theory of Islamic economics is expected to grow from Islamic doctrine or principle of economy and rooted in empirical facts. The methodology of Islamic economics play a role in integrating doctrine and empirical reality in the process of theorizing Islamic economics. This article describes the three sources of Islamic economic epistemology, the link between doctrine and reality, and the interaction and integration of doctrine and reality in the process of theorizing Islamic economics. Islamic economic theory that is born must have integrity and be tested on three dimensions: doctrine, rationality, and empirical experience.